ANTHROPOCENTRIC PHRASEOLOGICAL UNITS WITH A COMPOSITIONAL STRUCTURE IN ENGLISH AND UZBEK LANGUAGES - Jabbarova, Anora (Журнал иностранных языков и лингвистики, 2023)
An examination of adjectival phrases with a compositional structure shows that they are characterized by the ability to form words. This fact alone does not prove that these phrases are complex words, since the ability to form words is also characteristic of many variable combinations of words (cf. long hair - long-haired; strong mind - strong-minded; "many years" - "many years" etc.), which does not at all turn them into complex words, since these variable formations are characterized by separate forms (longer hair, longest hair, her hair is long, long and curly hair, etc.).